Digital Transformation Journey of SMEs in Indonesia During the Post Pandemic Era - Rizky, Agung; Gunawan, Ahmad; Santiago Ikhsan, Ramiro (APTISI Transactions on Management (ATM), 2025)
The COVID-19 pandemic marked a significant turning point for small and medium enterprises (SMEs) in Indonesia, compelling many to rapidly transi- tion from traditional offline operations to digital business models. This study aims to analyze the digitalization journey of SMEs in the post-pandemic era by examining the opportunities and challenges they encounter during this transformation. A descriptive qualitative approach was employed, using secondary data sourced from official reports such as BPS, the Ministry of Cooperatives and SMEs, and the economy SEA Report, complemented by relevant academic literature. The findings reveal that digitalization has opened substantial oppor- tunities for SMEs, including expanded market reach, improved operational ef- ficiency, and enhanced customer engagement through e-commerce platforms, digital payment systems, and social media marketing. However, persistent bar- riers remain, such as limited digital literacy, uneven internet infrastructure, high implementation costs, and consumer trust issues in online transactions. This study concludes that while digitalization offers a vital pathway for SME growth and resilience, addressing these barriers requires collaborative efforts among business owners, policymakers, and digital platform providers. Future research should employ quantitative methods and explore sector-specific case studies to deepen understanding of digital transformation strategies.